Monolithic CMOS-MEMS integration for high-g accelerometers - Narasimhan, Vinayak (2015)
This paper highlights work-in-progress towards the conceptualization, simulation, fabrication and initial testing of a silicon-germanium (SiGe) integrated CMOS-MEMS high-g accelerometer for military, munition, fuze and shock measurement applications. Developed on IMEC’s SiGe MEMS platform, the MEMS offers a dynamic range of 5,000 g and a bandwidth of 12 kHz. The low noise readout circuit adopts a chopper-stabilization technique implementing the CMOS through the TSMC 0.18 µm process. The device structure employs a fully differential split comb-drive set up with two sets of stators and a rotor all driven separately. Dummy structures acting as protective over-range stops were designed to protect the active components when under impacts well above the designed dynamic range.